IBM DS8880 high-performance Flash Enclosure Gen2 (DS8880 Release 8.5.1) - Manthorpe, Stephen; Toser, Tamas; Westphal, Axel (IBM redpaper., 2018)
This IBM® Redpaper"!publication describes the IBM DS8880 High-Performance Enclosure (HPFE) Gen2 architecture and configuration, as of DS8880 Release 8.51. The DS8880 HPFE Gen2 is a 2U Redundant Array of Independent Disks (RAID) flash enclosure with associated Flash RAID adapters that can be used exclusively with DS8880 models. The flash enclosure and Flash RAID adapters are installed in pairs. Each storage enclosure pair can support 16, 32, or 48 encryption-capable flash drives (2.5-inch, 63.5 mm form factor)